THE EFFECT OF STANDARD UNDERSTANDING OF GOVERNMENT ACCOUNTING, EXPERIENCE, AND ACCOUNTABILITY ON THE PERFORMANCE OF INSPECTORATE OFFICE STAFF IN RIAU PROVINCE - Sanusi Ariyanto (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2023)
The purpose of this study was to determine the effect of understanding government accounting standards, experience, and accountability on the performance of financial auditors at the  Riau Province Inspectorate. The variables in this study are the independent and dependent variables. The independent variables consist of understanding of accounting standards, experience, and accountability, while the dependent variable of this study is the performance of financial examiners. A descriptive method in the form of correlation studies with a quantitative approach is applied in this study to determine the effect between variables. The use of this method is expected to produce more accurate measurement results related to the responses given by respondents. The data in the form of numbers are then processed statistically by using validity, reliability tests, and hypothesis testing T and F. The population in this study was limited to only the financial examiners of the Riau Province Inspectorate. The research sample consisted of 34 financial examiners where they were given a questionnaire with a Likert scale. Data analysis was carried out at a significant level of 95% using regression analysis. The results of the analysis of this study found that the variables of experience, competence, and independence had a positive effect on performance. The t-test also revealed that experience, competence, and independence partially have a significant effect on performance. In the F test, the results show that experience, competence, and independence have a simultaneous effect on performance.